Phytochemical compounds with promising biological activities from Ascophyllum nodosum extracts using microwave-assisted extraction - Cassani, Lucía Victoria (2024)
Phytochemical-rich antioxidant extracts were obtained from Ascophyllum nodosum (AN) using microwave assisted extraction (MAE). Critical extraction factors such as time, pressure, and ethanol concentration were optimized by response surface methodology with a circumscribed central composite design. Under the optimalMAE conditions (3 min, 10.4 bar, 46.8 % ethanol), the maximum recovery of phytochemical compounds (polyphenols and fucoxanthin) with improved antioxidant activity from AN was obtained. In addition, the optimized AN extract showed significant biological activities as it was able to scavenge reactive oxygen and nitrogen species, inhibit central nervous system-related enzymes, and exhibit cytotoxic activity against different cancer cell lines. In addition, the optimized AN extract showed antimicrobial, and anti-quorum sensing activities, indicating that this extract could offer direct and indirect protection against infection by pathogenic microorganisms.This work demonstrated that the sustainably obtained AN extract could be an emerging, non-toxic, andnatural ingredient with potential to be included in different applications.